Computational and experimental identification of novel human imprinted genes - Luedi, Philippe P.; Dietrich, Fred S.; Weidman, Jennifer R.; Bosko, Jason M.; Jirtle, Randy L.; Hartemink, Alexander J. (Genome Research, 2007)
Imprinted genes are essential in embryonic development, and imprinting dysregulation contributes to human disease. We report two new human imprinted genes: KCNK9 is predominantly expressed in the brain, is a known oncogene, and may be involved in bipolar disorder and epilepsy, while DLGAP2 is a candidate bladder cancer tumor suppressor. Both genes lie on chromosome 8, not previously suspected to contain imprinted genes. We identified these genes, along with 154 others, based on the predictions of multiple classification algorithms using DNA sequence characteristics as features. Our findings demonstrate that DNA sequence characteristics, including recombination hot spots, are sufficient to accurately predict the imprinting status of individual genes in the human genome.
10.1101/gr.6584707